Seed vigour contributes to yield improvement in dry direct-seeded rainfed lowland rice - Yamane, K.; Garcia, R.; Imayoshi, K.; Mabesa-Telosa, R.C.; Banayo, N.P.M.C.; Vergara, G.; Yamauchi, A.; Sta. Cruz, P.; Kato, Y. (Wiley, 2018)
Dry direct‐seeded rice (DSR) cultivation is widely spreading in tropical Asia, but drought and nutrient deficiency stresses often cause crop failure in rainfed lowlands. The objective of this study was to dissect the physio‐morphological characteristics associated with crop establishment and early vigour of DSR under drought and P deficiency conditions in the Philippines. It was found that new drought‐resistant cultivars bred for DSR (Rc348 and Rc192) had faster germination and sprout growth than popular irrigated rice cultivars (Rc222 and Rc10) under soil water deficit due to rapid moisture acquisition by the germinating seeds from drying soils. There was a significant correlation between seed moisture content and the reduction in seed dry weight, and between reduction in seed dry weight and shoot elongation under both control and drought stress treatments at the germination stage. At the seedling stage, the root growth of Rc348 under drought tended to be more vigorous with its higher root‐to‐shoot ratio compared to Rc222 and Rc10. The seedling vigour of Rc348 under P deficiency was also greater than that of Rc222 due to its greater root growth and P uptake. The yields of Rc348 and Rc192 grown under rainfed condition at the target drought‐prone site where a dry spell of 13 days occurred during crop establishment were higher (4.0–4.1 t ha−1) than the yield of Rc10 (3.0 t ha−1). These results suggest that quick germination and seedling vigour with quick root anchorage and great nutrient uptake capacity, even with limitations of soil moisture and nutrients, would be important traits for DSR in rainfed lowlands.